Dancing Around Death: Hospitalist–Patient Communication About Serious Illness. (January 2013) - Anderson, Wendy G.; Kools, Susan; Lyndon, Audrey
Hospital physicians care for most seriously ill patients in the United States. We employed dimensional analysis to describe communication about death and dying in audio-recorded admission encounters between seriously ill patients and hospitalists. Acknowledging or not acknowledging the possibility of dying emerged as a key process. Acknowledgment was rare, and depended on synergistic communication behaviors between patient and physician. Facilitators included patients cuing for information and disclosing emotional distress, and physicians exploring the patient's understanding of his or her illness and emotional distress. When hospitalists focused on acute issues, stated that they were awaiting test results, and deferred to other physicians, discussion moved away from acknowledgment. Meaningful discussion of end-of-life issues, including goals and values, fears about death and dying, prognosis, and options for palliative care followed open acknowledgment. This acknowledgment process can serve as a guide for providers to sensitively and honestly discuss essential end-of-life issues.